2006
DOI: 10.1007/s00442-006-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Larval settlement of the common Australian sea urchin Heliocidaris erythrogramma in response to bacteria from the surface of coralline algae

Abstract: Bacterial biofilms are increasingly seen as important for the successful settlement of marine invertebrate larvae. Here we tested the effects of biofilms on settlement of the sea urchin Heliocidaris erythrogramma. Larvae settled on many surfaces including various algal species, rocks, sand and shells. Settlement was reduced by autoclaving rocks and algae, and by treatment of algae with antibiotics. These results, and molecular and culture-based analyses, suggested that the bacterial community on plants was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
149
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(158 citation statements)
references
References 67 publications
6
149
2
1
Order By: Relevance
“…Species belonging to this genus have been shown to induce settlement of the larvae of the hydrozoan Hydractinia echinata (Müller 1973, Seipp et al 2007) and the corals Acropora willisae and A. millepora (Negri et al 2001). The species Pseudoalteromonas luteoviolacea also induces metamorphosis in the larvae of the polychaete Hydroides elegans (Huang & Hadfield 2003) and the sea urchin Heliocidaris erythrogramma (Huggett et al 2006). Hence, the specificity of larval settlement in response to P. luteoviolacea may be due to unknown properties that are uniquely associated with this bacterial species, making it very inductive to a range of different invertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to this genus have been shown to induce settlement of the larvae of the hydrozoan Hydractinia echinata (Müller 1973, Seipp et al 2007) and the corals Acropora willisae and A. millepora (Negri et al 2001). The species Pseudoalteromonas luteoviolacea also induces metamorphosis in the larvae of the polychaete Hydroides elegans (Huang & Hadfield 2003) and the sea urchin Heliocidaris erythrogramma (Huggett et al 2006). Hence, the specificity of larval settlement in response to P. luteoviolacea may be due to unknown properties that are uniquely associated with this bacterial species, making it very inductive to a range of different invertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…DGGE data available on other marine macroalgae derived from rpoB based DGGE show differences in banding patterns among individuals of up to 16% for Amphiroa anceps, 30% for Corallina officinalis and 30% for Delisea pulchra (Huggett et al, 2006). Studies of sponge-associated bacteria based on DGGE analysis of the 16S rRNA gene reported differences in DGGE banding patterns of o30%, even for samples of the same species collected over a 500 km range (Taylor et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Components of biofilms such as bacteria and microalgae (e.g. diatoms) found on the surface of host organisms have demonstrated positive effects on the recruitment of marine invertebrates (Keough & Raimondi 1996, Huggett et al 2006. However, further research is needed to isolate the source of potential settlement cues.…”
Section: Discussionmentioning
confidence: 99%
“…Marine invertebrate larvae settle in response to a range of chemical and physical factors (see Burke 1986, Butman 1987, Pawlik 1992, Steinberg et al 2001 for reviews). Natural cues from biofilms (Keough & Raimondi 1996, Harder et al 2002, Huggett et al 2006, macroalgae (Morse & Morse 1984, Walters et al 1996, Swanson et al 2004) and conspecifics (Jensen & Morse 1990, Zimmer-Faust & Tamburri 1994 can induce settlement of invertebrates. Acceptance or rejection of a surface has also been correlated to the surface profile (roughness), including microtexture (Berntsson et al 2000, Scardino & de Nys 2004, Schumacher et al 2007 or the number of adhesion points an organism can make on a surface (Callow et al 2002, Scardino et al 2008.…”
Section: Introductionmentioning
confidence: 99%